EMPOWERING HOUSEWIVES THROUGH 3R (REDUCE, REUSE, RECYCLE) TRAINING TO REALIZE AN ENVIRONMENTALLY FRIENDLY VILLAGE - Maslihah, Sri; Nurendah, Gemala; Wyandini, Diah Zaleha; Kosasih, Engkos; Damaianti, Lira Fessia; Ihsan, Helli; Saefudin, Muhamad Arif (LPPM Univ. Ibn Khaldun Bogor, 2025)
A healthy environment is a crucial factor in supporting optimal child growth and development. In various regions of Indonesia, there are still many issues related to low awareness of healthy lifestyles that have not been properly addressed. The strategic role of housewives is essential in maintaining environmental cleanliness, but limited access to information and skills means some mothers are unable to properly manage household waste. This community service activity aims to empower housewives through 3R (Reduce, Reuse, Recycle) training. This training is the first step in realizing environmentally friendly villages. The methods used include counseling, waste management practices, and mentoring in implementing the 3Rs in households. It is hoped that housewives participating in the training will develop skills in sorting and processing household waste, and that a collective commitment to maintaining environmental cleanliness with the community will be formed.